Are vaccine shortages a relevant public health issue in Europe? Results from a survey conducted in the framework of the EU Joint Action on Vaccination. Issue 13 (18th March 2022) - Filia, Antonietta; Rota, Maria Cristina; Grossi, Adriano; Martinelli, Domenico; Prato, Rosa; Rezza, Giovanni
Highlights: We conducted a survey on vaccine shortages and stockouts in Europe in 2016–2019. Vaccine shortages and stockouts were reported by 19 of 21 surveyed countries. The vaccines most frequently affected were DT-containing and hepatitis B vaccines. The most commonly reported causes were production issues and global shortage. Vaccine shortages/stockouts had a relevant impact on vaccine services. Abstract: National immunisation programmes require an adequate supply of vaccines to function properly but many countries, globally and in Europe, have reported vaccine shortages. A comprehensive view of vaccine shortages and stockouts in the EU/EEA is missing in the published literature. This study was conducted in the framework of the European Joint Action on Vaccination (EU-JAV). Twenty-eight countries, including 20 EU-JAV consortium member states and an additional 8 EU/EEA countries, were invited to participate in a survey aimed at collecting information on vaccine shortages and stock-outs experienced from 2016 to 2019, their main causes, actions taken, and other aspects of vaccine supply. Twenty-one countries completed the survey (response rate 75%), of which 19 reported at least one shortage/stock-out event. Overall, 115 events were reported, 28 of which led to a change in the national immunisation programme. The most frequently involved vaccines were DT- and dT-containing combination vaccines, hepatitis B, hepatitis A, and BCG vaccines. The median duration of shortages/stock-outs was five months (range <1 month–39 months). Interruption in supply and global shortage were the most frequently indicated causes. Only about half of countries reported having an immunization supply chain improvement plan. Similarly, only about half of countries had recommendations or procedures in place to address shortages/stockouts. The survey also identified the occurrence of shortages/stockouts of other biological products (e.g. diphtheria antitoxin in 12 countries). Public health strategies to assure a stable and adequate vaccine supply for immunization programmes require coordinated actions from all stakeholders, harmonized definitions, strengthening of reporting and monitoring systems, the presence of an immunization supply chain improvement plan in all countries, and procedures or recommendations in place regarding the use of alternative vaccines or vaccination schedules in case of shortages/stockouts.